Prognostic Factors of Colorectal Cancer: A Comparative Study on Patients With or Without Liver Metastasis - Peng, Honghua; Liu, Guifeng; Bao, Ying; Zhang, Xi; Zhou, Lehong; Huang, Chenghui; Song, Zewen; Cao, Sudan; Dang, Shiying; Zhang, Jing; Huang, Tanxiao; Wu, Yuling; et al. (Frontiers in Oncology, 2021)
Background:Radical or palliative surgery with subsequent adjuvant therapy is the routine treatment for stage II/III colorectal cancer(CRC) and some stage IV CRC patients. This study aimed to clarify the prognostic clinicopathological and genetic factors for these patients. Methods:Fifty-five stage II-IV CRC patients undergoing surgery and adjuvant therapy were recruited, including patients without liver metastasis(5 at stage II, 21 at stage III) and with liver metastasis(29 at stage IV). Genetic alterations of the primary cancer tissues were investigated by WES. Patients were followed up to 1652 days(median at 788 days). Results:The mutational landscape of primary CRC tissue of patients with or without liver metastasis was largely similar, although the mutational frequency of TRIM77 and TCF7L2 were significantly higher in patients with liver metastasis. Several main driver gene co-mutations, such as TP53-APC, APC-KRAS, APC-FRG1, and exclusive mutations, such as TP53-CREBBP, were found in patients with liver metastasis, but not in patients without liver metastasis. No significant difference was found between the two groups in aberrant pathways. If stage II-IV patients were studied altogether, relapse status, SUPT20HL1 mutations, Amp27_21q22.3 and Del8_10q23.2 were independent risk factors(P<0.05). If patients were divided into two groups by metastatic status, surgery types and Amp6_20q13.33 were independent risk factors for patients without liver metastasis(P<0.05), while TRIM77 mutations were the only independent risk factor for patients with liver metastasis(P<0.05). Conclusions:Surgery types and Amp6_20q13.33 were independent risk factors for CRC patients without liver metastasis, and TRIM77 mutations were the independent risk factor for CRC patients with liver metastasis.